Nipple Trauma - Page-Goertz, Sallie; McCamman, Sarah (Sudbury, MA: Jones and Barlett, 1996)
Explore strategies for the care of a new teen mom who is experiencing nipple trauma. Learn how every intervention affects lactation physiology and how to effectively respond to concerns about breastfeeding myths. Information iregarding breastfeeding basics includes research basis for every management recommendation.
Best Beginnings Productions
System Requirements : 486 (Pentium Rrecommended), 8 MB RAM, 4X CD-ROM drive, QuickTime for windows 2.1.1
System Requirements : Macintosh: 68030 ('040 or PowerMac recommended), 8 MB RAM, 2 x CD-ROM drive (4 x speed or higher recommended), QuickTIme for windows 2.1.1
Keywords: Breast feeding; Infant nutrition; Nipples -- injuries